Manifestations Of Antisocial Behavior - Oymatova Dilorom Ro'zimurotovna; Elmurodova Sohiba (Euro Asian Journal Publishing, 2025)
This article explores the main forms of antisocial behavior, their impact on social life, and the underlying causes. Through examples such as deviant actions, criminality, aggression, and moral decline among youth, the manifestations of antisocial morality are analyzed. The paper also highlights the role of family, school, and community in preventing such behaviors, emphasizing effective pedagogical strategies for intervention
Keywords: Antisocial morality; deviant behavior; criminality